PERAN ORANG TUA DALAM MEMOTIVASI ANAK UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - Naura Qistina Wardah Theofani; Sartika; Muhammad Wahyudi (Jurnal At-Tabayyun, 2022)
The Role of Parents in Motivating Children to Continue Higher Education". There are two issues studied in this journal, 1). what is the role of parents in motivating children to continue their education to higher education (a case study in Pengkolan Village, Bosar Maligas District, Simalungun Regency). 2). What factors support and hinder parents in motivating their children to continue their education to higher education (a case study in Pengkolan Village, Bosar Maligas District, Simalungun Regency). The purpose of this study was to find out and describe the role of parents in motivating children to continue their education to tertiary institutions in Pengkolan Village, Bosar Maligas District, Simalungun Regency. and to describe the supporting and inhibiting factors of parents in motivating children to continue their education to higher education in Pengkolan Village, Bosar Maligas District, Simalungun Regency. To explore the problems in this study, the researchers used a type of field research with a qualitative approach and the method used was Descriptive Analytic. Determination of informants using purposive sampling.